Comparative Genomic Analysis of Labrenzia aggregata (Alphaproteobacteria) Strains Isolated From the Mariana Trench: Insights Into the Metabolic Potentials and Biogeochemical Functions - Zhong, Haohui; Sun, Hao; Liu, Ronghua; Zhan, Yuanchao; Huang, Xinyu; Ju, Feng; Zhang, Xiao-Hua (Frontiers in Microbiology, 2021)
Hadal zones are marine environments deeper than 6,000 m, most of which comprise oceanic trenches. Microbes thriving at such depth experience high hydrostatic pressure and low temperature. The genomics and adaptation mechanisms of these microbes to such extreme environments are largely unknown. Here, we compare five complete genomes of bacterial strains belonging to Labrenzia aggregata (Alphaproteobacteria), including four from the Mariana Trench at depths up to 9,600 m and one reference from surface seawater of the East China Sea, to uncover the genomic potentials of this species. Genomic investigation suggests all the five strains of L. aggregata as participants in nitrogen and sulfur cycles, including denitrification, dissimilatory nitrate reduction to ammonium (DNRA), thiosulfate oxidation and dimethylsulfoniopropionate (DMSP) biosynthesis and degradation. Further comparisons show that, among the five strains, 85% gene functions are similar with 96.7% of them encoded on the chromosomes, whereas the numbers of functional specific genes related to osmoregulation, antibiotic resistance, viral infection and secondary metabolite biosynthesis are majorly contributed by the differential plasmids. A following analysis suggest the plasmidic gene numbers increase along with isolation depth and most plasmids are dissimilar among the five strains. These findings provide a better understanding of genomic potentials in the same species throughout a deep sea water column and address the importance of externally originated plasmidic genes putatively related to deep-sea adaptation.